Inclusive Education Strategies for Achieving Learning Outcomes for Bajo Children at PKBM Ula-Ula Nusantara - Aswading; Yatim Riyanto; Sjafiatul Mardliyah (Universitas Negeri Semarang, 2026)
Inclusive education provides opportunities for every student, including Bajo children, to receive educational services tailored to their needs and potential. This study aims to describe the inclusive education strategy at the Ula-Ula Sama Nusantara Community Learning Center (PKBM) and identify supporting and inhibiting factors for its implementation. The method used was a qualitative approach using interviews, observation, and documentation techniques, involving the PKBM head, the deputy head of curriculum, tutors, students, and parents. The results showed that the inclusive education strategy includes flexible curriculum adjustments, life skills-based learning, and strengthening character and social skills. Supporting factors include a flexible curriculum and tutor commitment, while inhibiting factors include limited facilities, tutor competence, and suboptimal parental support. In conclusion, the strategy creates an adaptive and participatory learning environment, supporting the non-academic learning outcomes of Bajo children.